1 ANALISIS PENGARUH PERTUMBUHAN ASSET, PROFITABILITAS, PERTUMBUHAN PENJUALAN DAN KEBIJAKAN DIVIDEN TERHADAP KEPUTUSAN PENDANAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putri Ayulestari; Kirmizi '; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of asset growth, profitability, sales growth and dividend policy on funding decisions at companies listed on the Indonesia Stock Exchange. With samples are 26 companies listed in Indonesia Stock Exchange (BEI) in the year 2007-2012. The analytical method used is multiple regression analysis. Before the t test statistic for multiple regression equation, the test is done first classical assumption of data normality, autocorrelation, multicollinearity and heteroscedasticity. Once the data is free from classical assumptions, then the hypothesis test using the t test to see the effect of each independent variable on the dependent variable partially. Based on the analysis, it is known that the growth in assets, profitability, and sales growth proved significant effect on DER. The dividend policy of no significant effect on DER. The coefficient of determination is a study in which 58.2 % 42.8 % further change in the dependent variable that is influenced by other variables not included in this study. Keywords : Debt to Equity Ratio, Asset Growth, Profitability, Sales Growth, Dividend Policy